2017
DOI: 10.1080/09537287.2017.1381887
|View full text |Cite
|
Sign up to set email alerts
|

Business Performance Analytics: exploring the potential for Performance Management Systems

Abstract: Business Performance Analytics (BPA) entails the systematic use of data and analytical methods (mathematical, econometric, statistical) for performance measurement and management. Although potentially overcoming some traditional diagnostic issues related to Performance Management Systems (PMS), such as information overload, absence of cause-effect relationships, lack of a holistic view of the organization, research in the field is still in its infancy. A comprehensive model for operationalising analytics for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 81 publications
2
61
0
Order By: Relevance
“…From this starting point, and because it focusses on BM improvement and not on BM Innovation, we aggregated several points of the literature to form the artifact. Examples included learning from performance management [16], experimentation through trial-and-error [3,9], understanding the value of web analytics [91], and leveraging the big data context for customer-driven orientation [19].…”
Section: The Methods For Data-driven Business Modelingmentioning
confidence: 99%
“…From this starting point, and because it focusses on BM improvement and not on BM Innovation, we aggregated several points of the literature to form the artifact. Examples included learning from performance management [16], experimentation through trial-and-error [3,9], understanding the value of web analytics [91], and leveraging the big data context for customer-driven orientation [19].…”
Section: The Methods For Data-driven Business Modelingmentioning
confidence: 99%
“…LaValle et al 2011noted that top-performing organizations use analytics five times more than low performers. Raffoni et al (2018) argue that big data analytics, if used cautiously, can help the organization to achieve better performance. Akter et al (2016) argue that big data analytics capability has a positive impact on organizational performance.…”
Section: Big Data Analytics Capability and Competitive Advantagementioning
confidence: 99%
“…Hence, there have been an increasing number of studies in the last years reflecting on the challenges of performance measurement system in the context of industrial revolution. Raffoni et al (2018) explored the potential of performance management systems and indicated that Business Performance Analytics (BPA) can contribute to identifying critical performance variables, potential sources of risk and related interdependencies. Sangwa and Sangwan (2018) developed performance measurement framework for lean organizations and identified the seven categories representing all organizational functions, dividing into 26 performance dimensions and key performance indicators (KPIs) for each performance dimension in the context of lean principles.…”
Section: Theoretical Arguments To Analyse Performance Measurement In mentioning
confidence: 99%
“…Wamba et al (2015) generally indicated that organizations need to leverage the information eco-system arising out of the BD adoption to share the real time information, better understand customers, optimize supply chains and human resources, improve financial metrics and develop the critical insights for decision making. In relation to the scientific literature review could be stated that different Industry 4.0 clusters have been researched in the context of performance measurement such as Big Data, IoT, analytics digitalization and human -machine interaction (Raffoni et al, 2018;Papadopoulos et al, 2017;Van der Stede, 2016;Schoenherr & Speier-Pero, 2015;Hazen et al, 2014;Waller & Fawcett, 2013). Also it could be noted that the literature is still lacking an understanding of the main changes and developments of performance measurement system in the context of industrial revolution as different studies are fragmented, analyse a separate function of performance measurement (Raffoni et al, 2018;Trstenjaka & Cosic, 2017;Papadopoulos et al, 2017) or are limited to a specific context (Sangwa & Sangwan, 2018).…”
Section: Theoretical Arguments To Analyse Performance Measurement In mentioning
confidence: 99%
See 1 more Smart Citation